(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In Brazil, has been made campaigns to vaccinate dogs and cats once a year in almost all municipalities and these animals are among the main transmitters of rabies to humans. The presence of rabies antibodies in animals is likely a good indicator that they are immunized and protected this zoonosis.